Die Ausbreitung des mechanischen Vollerntens für Industrietomaten in Kalifornien.: Eine agrartechnologische Innovation und ihre Wirkungen - Windhorst, Hans-Wilhelm (ERDKUNDE, 1990)
California has become the leading state in the production of processing tomatoes. Since 1960 the regional concentration has been occurring and has led to the fact that this state had a share of about 90 % of the total U.S. production in 1987. This success is closely related to the development and spatial diffusion of two innovations, the mechanical tomato harvester and a tomato variety that can be harvested by these machines. Within only ten years (1960 1970) the innovation of the mechanical harvester completely changed the harvesting process, as hand picking was abandoned because of higher costs. The diffusion process has led, as can be shown, to far reaching socio-economic changes in the Central Valley of California. This is especially true for the composition of the workers in tomato production and the size structure of tomato-growing farms. The regional concentration in the valley has also led to ecological impacts in the Westlands, as the irrigation process caused drainage problems and an increase of salt and selenium in the drainage water. The major drain had to be shut down, which again led to a rise of the shallow ground water table in some areas. The diffusion of the mechanical harvester had far reaching effects on the spatial distribution of tomato growing in the U.S. Because of smaller farm units on which the harvester could not be used economically, the East and Midwest lost their once leading position. On the other hand the San Joaquin Valley, here again Fresno County, constantly increased its share in the production of processing tomatoes.